EFEKTIVITAS MODEL ROLE PLAYING DALAM MENINGKATKAN KOMPETENSI MAHASISWA PADA MATA KULIAH MANAJEMEN KEUANGAN - Tiara Anggia Dewi (PROMOSI: Jurnal Program Studi Pendidikan Ekonomi, 2017)
One of the direct learning models involved students in the learning process is the Role Playing model. The learning model is very suitable for learning subjects that involves real life situation. In Model Role Playing students are invited to play some roles related to the subjects being studied. With the role played by each student, they can experience firsthand the lessons exposed to the subjects. For example on financial management subjects. This research is an experimental, with research design True Experimental Design, Pretest-control Group Design. In the data analysis can be seen that the calculation of the value analysis thitung> ttabel. On the list of significant 5% that is 7.74> 1.70 that t_hitung bigger than ttable and at a significant level of 1% that is 7.74> 2.46 that thitung bigger than ttabel. By affecting t_count with ttable if t_count> ttable means the hypothesis is accepted. From these tests it can be concluded that the effectiveness of Role Playing Model in Improving Student Competence on Financial Management Subject, the hypothesis is accepted. Keywords: Financial Management, Learning, Role Playing Model,